P207 Self-fill oxygen systems – benefits for patients, healthcare providers and the environment. (15th November 2016) - Murphie, P; Little, S; Setters, J; Hex, N
Abstract : Introduction: 'Non-delivery' Home oxygen concentrator systems that allow self-filling of ambulatory oxygen (AO) cylinders are emerging. They offer a relatively unlimited supply of AO in suitably assessed people who require Long term oxygen therapy (LTOT) with the proviso that they can use these systems safely and effectively, thus allowing users of LTOT to be self-sufficient and facilitating longer periods of time away from their home. Methods: A national review of the home oxygen service in Scotland was undertaken resulting in consolidation of all home oxygen delivery systems under a single contractor with the transition to this new service delivered over 2013. A health economics analysis was conducted following the transition to compare the differences between the previous conventional AO cylinder home delivery service and the HomeFill (HF) system. Results: Conservative calculations indicate a cost for 3 AO cylinders of about £84 per week, or £4247 per year, compared with a cost for HF of £920 per annum, giving a benefit of around £3344 for each patient. The costs savings related to reduced travel and delivery in 1213 HF users compared to the AO cylinder delivery model is 1.25 million Km's and the estimated carbon emission (CO2 e) reduction for the HF system is 261.29 tonnes of CO2 e. Conclusion: Evidence is emerging that 'Self-fill'/'non-delivery' oxygen systems can meet the AO needs of many patients using LTOT and can have a positive impact on quality of life; increased time spent away from place of residence and can offer significant financial savings to health care providers. Even with conservative estimates in the health economics analysis, the provision of the HF system to around 1000 patients saves about £1.67 million per year in Scotland. Self-fill oxygen delivery systems have been available in the UK for >5 years and whilst one could argue for a larger randomised controlled trial, the authors would propose that with the available evidence, particularly the financial impact, it should be more widely utilised.